Percepções dos servidores técnico-administrativos em educação sobre o teletrabalho na Universidade Federal de Mato Grosso - Zanini, Iolanda Francione (2024)
This work aims to identify perceptions of technical-administrative employees about work, considering the teleworking pilot project at the Federal University of Mato Grosso. The pilot project was part of the initial phase of the implementation of the Brazilian Federal Government's Management and Performance Program (PGD), started in December 2022 and completed in the second half of 2023. For the analysis, a literature review was carried out on the transformations of the work, transformations in public administration in Brazil and the type of teleworking in the public and private, national and international context. An analysis of the perception of technical-administrative employees participating in the pilot project and their managers regarding teleworking was also carried out from a qualitative perspective. The results showed that teleworking is a reality that will continue to expand in the public service. The perception of employees involved in the pilot project at the Federal University of Mato Grosso (UFMT) indicated benefits in this new work organization, as well as problems to be overcome. The study proves to be relevant for developing knowledge about the consequences of implementing teleworking, as well as its potential and limitations in the context of a public higher education institution.